Making Fish Culture Sustinable - Flynn, Ph.D., Dave (Archives of Business Research, 2017)
The challenges facing the population of fish throughout the world are critical. Overfishing, physical impediments, and the warming of the world oceans are threatening the population that includes small krill, tuna, trout, salmon, and whales. Some scientists predict that by 2050, the oceans could be fishless. Various solutions are being sought and some have been implemented that include conservation, the removal of dams on rivers, and aquaculture for ocean salmon and tuna. Aquaculture refers to the breeding, rearing, and harvesting of plants and animals in all types of water environments. Marine aquaculture refers to the culturing of species that live in the ocean. Herein, we explore the various threats to fish populations and efforts to mitigate them, especially in Japan.